2014
DOI: 10.1088/0031-8949/89/8/085403
|View full text |Cite
|
Sign up to set email alerts
|

L-shell electron excitations of Mg- through O-like tungsten ions

Abstract: Electron impact excitations from ground state L shell viz. n = 2 → n = 3 transitions in Mg-like W62+, Na-like W63+, Ne-like W64+, F-like W65+ and O-like W66+ ions have been considered. A fully relativistic distorted wave (RDW) theory has been used to calculate the excitation cross-sections for an electric and magnetic dipole, as well as for the quadrupole transitions for these ions, which were observed recently in the measurements taken from an electron-beam-ion trap (EBIT-I) at the Livermore laboratory. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…A collisional-radiative model was applied to explain the observed spectrum. An MCDF calculation with restricted electron correlation effects on the 3d-3p transitions was presented by Dipti et al; they also calculated the electron impact excitation cross section and polarization degree [12].…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A collisional-radiative model was applied to explain the observed spectrum. An MCDF calculation with restricted electron correlation effects on the 3d-3p transitions was presented by Dipti et al; they also calculated the electron impact excitation cross section and polarization degree [12].…”
Section: Modelmentioning
confidence: 99%
“…During recent decades, several studies have been performed to provide the theoretical and experimental values of W 54+ ions [5][6][7][8][9][10][11][12]. Safronova et al calculated the magnetic dipole (M1) and electric quadrupole (E2) transitions between the multiplets of the ground state configuration ([Ne]3s 2 3p 6 3d 2 ) of W 54+ using the relativistic many-body perturbation theory (RMBPT) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Within the frame of the tungsten collisions project reviewed in this communication, processes described by Equations (1)- (5) were studied for selected charge states by experiments which were partially accompanied by theory. In addition to information about the collision processes listed above, cross sections and rate coefficients for charge transfer ( [18,19] and references therein), electron-impact excitation ( [20,21] and references therein) together with spectroscopic information ( [22] and references therein) on tungsten ions in all charge states are needed for plasma diagnostics. Spectroscopic observations and further collisional data are becoming available now and are summarized in several contributions to the present Special Issue of ATOMS on "Atomic Data for Tungsten".…”
Section: Introductionmentioning
confidence: 99%
“…This ensures the quality of the target ion's wavefunctions that are crucial in determining the accuracy of the scattering parameters. Moreover, the RDW method has been successfully implemented in the previous work on a variety of targets from closed to open-shell systems and neutral atoms to multiply or highly charged ions atoms/ions [25][26][27][28][29][30]. It has also been found that using RDW cross sections in a collisional radiative (CR) model provides plasma parameters that are in better agreement with the measurements [31][32][33][34].…”
Section: Cross Sections and Rate Coefficientsmentioning
confidence: 97%